2014
DOI: 10.1007/s00248-014-0488-0
|View full text |Cite
|
Sign up to set email alerts
|

Soil Moisture and pH Control Relative Contributions of Fungi and Bacteria to N2O Production

Abstract: Fungal N(2)O production has been progressively recognized, but its controlling factors remain unclear. This study examined the impacts of soil moisture and pH on fungal and bacterial N(2)O production in two ecosystems, conventional farming and plantation forestry. Four treatments, antibiotic-free soil and soil amended with streptomycin, cycloheximide, or both were used to determine N(2)O production of fungi versus bacteria. Soil moisture and pH effects were assessed under 65-90 % water-filled pore space (WFPS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
53
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(58 citation statements)
references
References 84 publications
(98 reference statements)
4
53
0
Order By: Relevance
“…Liu et al (2010) also observed that the decreased expression of the N 2 O reductase was associated with the increased product ratio of N 2 O to N 2 under acidic conditions (Liu et al, 2010). The additional explanation of high HD-derived N 2 O in acid soils is that fungal communities could predominate in these acid soils and were responsible for the increase in N 2 O production, due to denitrifying fungi generally lack the nosZ gene and therefore contribute to higher heterotrophic denitrification-derived N 2 O production (Philippot et al, 2011;Chen et al, 2015a).…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al (2010) also observed that the decreased expression of the N 2 O reductase was associated with the increased product ratio of N 2 O to N 2 under acidic conditions (Liu et al, 2010). The additional explanation of high HD-derived N 2 O in acid soils is that fungal communities could predominate in these acid soils and were responsible for the increase in N 2 O production, due to denitrifying fungi generally lack the nosZ gene and therefore contribute to higher heterotrophic denitrification-derived N 2 O production (Philippot et al, 2011;Chen et al, 2015a).…”
Section: Discussionmentioning
confidence: 99%
“…However, other biotic/abiotic processes, such as nitrification, ammonia oxidation (Zhu, Burger, Doane, & Horwath, 2013), nitrifier denitrification (Zhu, Burger, et al, 2013), feammox (Ding, An, Li, Zhang, & Zhu, 2014), and chemical denitrification (Matocha, Dhakal, & Pyzola, 2012), may also contribute to soil N 2 O emission, and the influencing mechanisms of soil pH in these processes are still not clear. Moreover, shifts in soil pH may lead to significant changes in microbial community structure (Chen, Mothapo, & Shi, 2015;Fierer & Jackson, 2006;Hu, Zhang, Dai, Di, & He, 2013;Lauber, Hamady, Knight, & Fierer, 2009), the importance of these processes in N 2 O emission are then expected to be varied with soil pH.…”
Section: Differentiated Influences On N 2 O Emissionmentioning
confidence: 99%
“…However, only recently have abiotic factors, such as soil pH, redox potential, and water content proved to be important controlling factors for the leading roles of fungi versus bacteria in N 2 O production. In general, fungi dominate bacteria in N 2 O production under sub-anoxic conditions, and vice versa under strict anaerobic conditions (Seo and DeLaune, 2010;Chen et al, 2015). Fungi and bacteria also show different pH preferences in leading soil N 2 O emissions, with fungi prevailing at acidic pH and bacteria at neutral and alkaline pH (Herold et al, 2012;Chen et al, 2015).…”
Section: Introductionmentioning
confidence: 98%
“…In general, fungi dominate bacteria in N 2 O production under sub-anoxic conditions, and vice versa under strict anaerobic conditions (Seo and DeLaune, 2010;Chen et al, 2015). Fungi and bacteria also show different pH preferences in leading soil N 2 O emissions, with fungi prevailing at acidic pH and bacteria at neutral and alkaline pH (Herold et al, 2012;Chen et al, 2015). A correlation analysis suggests that the relative importance of fungi versus bacteria for soil N 2 O emissions is related to the predominant growth and activity of fungi and bacteria under corresponding environmental conditions (Chen et al, 2015).…”
Section: Introductionmentioning
confidence: 99%